A study of lamp with 365nm radiation uvled for the sterilization of bacteria - Nguyen Văn Hiếu; Vu Thế Đảng (Journal of Technical Education Science, 2011)
We studied and designed the lamp of LED with 365nm of ultraviolet wavelength for e.coli bacteria sterilization. The pulse width modulation (PWM) was used to control the radiation intensity of UVLEDs with micro controller. We studied the possiblity of sterilization of E.coli bacteria with the change of time and intensity radiation. The microorganism tests revealed that E.coli bacteria was killed with different levels. This device will be useful to sterilize the bacteria in water and others in next time.